Associations of cardiac injury biomarkers with risk of peripheral artery disease: The Multi-Ethnic Study of Atherosclerosis. (1st December 2021) - Garg, Parveen K.; Lima, Joao; deFilippi, Christopher R.; Daniels, Lori B.; Seliger, Stephen L.; de Lemos, James A.; Maisel, Alan S.; Criqui, Michael H.; Bahrami, Hossein
Abstract: Introduction: We investigated the associations of high-sensitivity cardiac Troponin T (hs-cTnT) and N-terminal pro B-type natriuretic peptide (NT-proBNP) levels with risk of developing clinical peripheral artery disease (PAD) or a low ankle–brachial index (ABI). Methods: Hs-cTnT and NT-proBNP were measured in 6692 and 5458 participants respectively without baseline PAD between 2000 and 2002 in the Multi-ethnic Study of Atherosclerosis. A significant number also had repeat biomarker measurement between 2004 and 2005. Incident clinical PAD was ascertained through 2017. Incident low ABI, defined as ABI <0.9 and decline of ≥0.15 from baseline, was assessed among 5920 eligible individuals who had an ABI >0.9 at baseline and at least one follow-up ABI measurement 3–10 years later. Multivariable Cox proportional hazards and logistic regression modeling were used to determine the association of these biomarkers with clinical PAD and low ABI, respectively. Results: Overall, 121 clinical PAD and 118 low ABI events occurred. Adjusting for demographic and clinical characteristics, each log unit increment in hs-cTnT and NT-proBNP was associated with a 30% (adjusted hazard ratio (HR) 1.3, 95% confidence interval (CI): 1.1, 1.6) and 50% (HR) 1.5, 95% CI: 1.2, 1.8) higher risk of clinical PAD respectively. No significant associations were observed for incident low ABI. Change in these biomarkers was not associated with either of the PAD outcomes. Conclusions: NT-proBNP and hs-cTnT are independently associated with the development of clinical PAD. Further study should determine whether these biomarkers can help to better identify those at higher risk for PAD. Highlights: Hs-cTnT and NT-proBNP levels are associated with an increased risk of PAD in predominantly white populations. We expanded these findings to a multi-ethnic cohort without baseline cardiovascular disease. Future studies are needed to determine whether these biomarkers can actually improve PAD risk prediction.